PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 41 BENGKALIS KECAMATAN BENGKALIS - Mahdamisa, Mahdamisa; Lazim.N, Lazim.N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Background problem in this research is the lack of science student learning outcomes, can be seen in student scores of 24 students who did not complete reach KKM (minimum completeness criteria) 7 students (29.16%) of 17 students (70.83) with a value the average grade 46.25. Based on these problems, the researchers have conducted research by using the method of classroom action research (PTK) by applying Cooperative Learning Model Cycle I Example Non Example. For the first cycle meeting 45.83% although the second meeting with kategori less.for the cycle meeting average increased to 66.67% with well categories.for cycle II to III meeting average increased average to 83.33% and the fourth meeting increased to 91.67% with the category of very good.the students in the first cycle of the first meeting of 54.17% with unfavorable category at the meeting to II increased to 62.50% with less category althought. At activitedmeeting on the second cycle althougt increased to 79.17% and fourth meeting to meeting increased to 91.67% with the category of very good.the average students learning outcomes is the application of 49.58 increased to 54.37 in the first cycle, and increased again to 69.79 in the second cycle. while classical completeness in the first cycle and the second cycle reached. Application cooperative learning model examples of non examples can improve learning outcomes sains elementary School fourth grade students 41Bengkalis.Key Words: Cooperative Model Type Non Examples Examples, Results learn science